Pengaruh sertifikasi guru terhadap kinerja guru SMPN 1 Durenan - Sunanik, Sunanik (Universitas Nusantara PGRI Kediri, 2015)
Teacher certification is the process of granting certificates to the teacher educators. Teaching certificate awarded to teachers who have met the professional standards of teachers. One purpose of certification is to improve the process and quality of education. (a) how the performance of the teachers have graduated and are not yet certified?, (b) whether there is a difference between the performance of teachers who already tersetifikasi with yet ?, (c) whether the usage allowance in accordance with its purpose?. Conclusions showed the performance of teachers SMPN1 Durenan already certified on average very well with the average value of 81. Performance SMPN 1 Durenan teacher who has not been certified on average very well with the average value of 76. There are differences in teacher performance SMPN1 Durenan already certified by a yet certified. The performance difference is caused by the experience, employment status and Educators Professional development opportunities profesi.Tunjangan average is used for children's education expenses, savings, subsistence, housing construction, purchase a lap top / computer, purchase books, and research activities / seminars.